El mediador intercultural de los medios de comunicación: una apuesta por el cambio social - Sobrados León, Maritza; Muñoz Chacón, Patricia (Mediaciones Sociales, 2009)
The population configuration of Spanish society, with 11% foreigners, demands a relationship between its members away from conflict and based on collaboration and mutual understanding. In this objective, the media have emerged as key parts for its ease to influence citizens. To optimize this role, the Office of Intercultural Communication Studies, established in Seville in 2006, within the Project Bembea, made a proposal for the creation of the intercultural mediator of the media, an expert of social mediation, as well as in the journalistic techniques. This figure would be the bridge of understanding between immigrants and reporters necessary to bring into society the reality of these groups beyond the institutional discourse.